Testing the Structural Model of the Relationship Between Metacognitive Deficits, Social Cognition, and Executive Functions With Dysfunction in Patients With Schizophrenia Considering the Mediating Role of Intrinsic Motivation - Zandasta, Elham; Haji Alizadeh, Kobra; Seddigh, Seyed Hamzeh (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: This study aimed to investigate the structural model of the relationship between metacognitive deficits, social cognition, and executive functions with cognitive dysfunction in patients with schizophrenia, considering the mediating role of intrinsic motivation.Methods and Materials: The research employed a descriptive-analytical and applied design. The statistical population consisted of 789 patients with schizophrenia in Bandar Abbas, from which 400 participants were selected using Cochran's formula and simple random sampling. Measurement tools included a researcher-developed questionnaire and three standardized instruments: Nejati’s Cognitive Abilities Questionnaire, the Barkley Deficits in Executive Functioning Scale (BDEFS), and the McAuley Intrinsic Motivation Inventory. Content validity was confirmed by psychology experts, and construct validity was verified via confirmatory factor analysis (CFA). Reliability was assessed using Cronbach’s alpha, composite reliability (CR), and average variance extracted (AVE). Data were analyzed using Pearson correlation, regression analysis, and structural equation modeling (SEM), with bootstrapping applied to examine the mediating effect of intrinsic motivation.Findings: Results demonstrated significant positive correlations between all core variables: metacognitive deficits, social cognition, executive functions, intrinsic motivation, and cognitive dysfunction. Regression analysis showed that metacognitive deficits (β = 0.273, p < .001), social cognition (β = 0.363, p < .001), and executive functions (β = 0.256, p < .001) significantly predicted dysfunction, while intrinsic motivation did not have a direct significant effect (β = 0.095, p = .084). However, intrinsic motivation significantly mediated the relationship between metacognitive deficits and dysfunction (indirect effect = 0.175, 95% CI [0.093, 0.245], p = .004).Conclusion: The findings confirm that metacognitive deficits, social cognition, and executive functions are significant predictors of dysfunction in patients with schizophrenia, with intrinsic motivation playing a meaningful mediating role in the pathway from metacognitive deficits to dysfunction. These results highlight the importance of cognitive and motivational factors in therapeutic interventions for schizophrenia.